RADIOGRAPHY TECHNIQUE OF OSSA PELVIS WITH SUSPECTED FRACTURE OF RAMUS PUBIS AT EFARINA ETAHAM HOSPITAL, BERASTAGI KARO DISTRICT 2021 - Awan Pelawi; Bambang Kustoyo; Sabrina Suci Zasneda; Sihat Manisia Siboro; Rian riko siringoringo (PT. Radja Intercontinental Publishing, 2022)
Fracture is a broken bone, a break in bone tissue that is commonly caused by forced injuries. The cause of fracture is an accident, be it a work accident, traffic accident. Broadly speaking, fractures are divided into three types, namely closed fractures, closed fractures, and complex fractures. The examination aims to determine the results of radiographic images, if there is a fracture or dislocation and is caused by KLL factors (traffic accidents). The aim of the study was to find out how the radiographic examination technique of Ossa Pelvis with the suspicion of a Ramus Pubis Fracture at the Radiology Installation of Efarina Berastagi Hospital in 2021. This type of research is descriptive research with data collection techniques by observation, documentation study and literature (library) study. The results of the examination of the Ossa Pelvis with the suspicion of a Ramus Pubis Fracture at the Radiology Installation of Efarina Etaham Berastagi Hospital are generally using AP (Anterior Posterior) projections using conventional X-rays. The x-ray film used is a high speed type combined with a fast screen intensifying (IS) where this type of intensifying screen (IS) film can produce images with good detail and sharpness. Thus the radiation dose can also be reduced for the patient and the operator himself. The film washing process should use Automatic Processing. It is hoped that it can be used as a reference for radiographic results, especially in cases of Ramus Pubis Fractures.